Association of early menopause with indoor air pollution: A multilevel modelling analysis of the nationally representative cross-sectional study in India - Pritam Halder; Anamika Soni; Ashwani Seth; Dheenadahayalan Vijayakumar; Anamika Das; Sujata Sankhyan; Anshul Mamgai; Saumyarup Pal; Jaya Tiwari; Aparna Baranwal; CM Chaitra (Journal of Family Medicine and Primary Care)
Background: Early onset of menopause poses a risk for various health issues in women. This study aimed to primarily examine the link between early menopause and indoor air pollution (IAP) and demonstrate this association within the Indian population, considering their place of residence. Methods: This longitudinal study included 24,862 eligible participants out of 73,000 surveyed. Logistic regression analyses, both crude and adjusted odds ratios (aOR), were used to examine the association between early menopause and various sociodemographic factors, IAP, and place of residence (rural/urban). Results: The study identified a significant correlation between early menopause and body mass index (BMI), educational status, marital status, occupation, physical activity, self-rated health, and smoking status. Women using unclean fuels did not show increased odds of early menopause (aOR: 1.00, 95% confidence interval [CI]: 0.93-1.08). Poor ventilation was linked to a slightly higher incidence (28.1% vs. 26.9%, aOR: 1.07, 95% CI: 0.99-1.15). Exposure to pollution-generating sources was significantly associated with early menopause (28.8%, aOR: 1.10, 95% CI: 1.02-1.18), especially in urban areas (aOR: 1.17, 95% CI: 1.01-1.36) but not rural (aOR: 1.08, 95% CI: 0.99-1.17). Indoor smoking was linked to higher odds (aOR: 1.09, 95% CI: 1.02-1.17), particularly in rural areas (aOR: 1.09, 95% CI: 1.01-1.18). Overall, IAP was significantly associated with early menopause (aOR: 1.07, 95% CI: 1.01-1.15). Conclusion: The findings reveal that IAP, from sources such as smoke and pollutants, significantly increases the risk of early menopause among Indian women. Urban women are more affected by pollution, whereas indoor smoking impacts both urban and rural women. Enhancing indoor air quality could reduce early menopause and improve women’s health in India.